A Comparison of Microfluidic-Jet Spray Drying, Two-Fluid Nozzle Spray Drying, and Freeze-Drying for Co-Encapsulating β-Carotene, Lutein, Zeaxanthin, and Fish Oil - Yongchao Zhu; Yaoyao Peng; Jingyuan Wen; Siew Young Quek (Foods, 2021)
Various microencapsulation techniques can result in significant differences in the properties of dried microcapsules. Microencapsulation is an effective approach to improve fish oil properties, including oxidisability and unpleasant flavour. In this study, β-carotene, lutein, zeaxanthin, and fish oil were co-encapsulated by microfluidic-jet spray drying (MFJSD), two-fluid nozzle spray drying (SD), and freeze-drying (FD), respectively. The aim of the current study is to understand the effect of different drying techniques on microcapsule properties. Whey protein isolate (WPI) and octenylsuccinic anhydride (OSA) modified starch were used as wall matrices in this study for encapsulating carotenoids and fish oil due to their strong emulsifying properties. Results showed the MFJSD microcapsules presented uniform particle size and regular morphological characteristics, while the SD and FD microcapsules presented a large distribution of particle size and irregular morphological characteristics. Compared to the SD and FD microcapsules, the MFJSD microcapsules possessed higher microencapsulation efficiency (94.0–95.1%), higher tapped density (0.373–0.652 g/cm3), and higher flowability (the Carr index of 16.0–30.0%). After a 4-week storage, the SD microcapsules showed the lower retention of carotenoids, as well as ω-3 LC-PUFAs than the FD and MFJSD microcapsules. After in vitro digestion trial, the differences in the digestion behaviours of the microcapsules mainly resulted from the different wall materials, but independent of drying methods. This study has provided an alternative way of delivering visual-beneficial compounds via a novel drying method, which is fundamentally essential in both areas of microencapsulation application and functional food development.